The Development of Digital Competencies in Pre-Service Teachers - Elma Marais (Research in Social Sciences and Technology, 2023)
Even before the Covid-19 pandemic created a historic pivotal moment for teacher training programmes on a global scale, the development of digital competencies has been regarded as a focal point for teachers. Tertiary institutions had just become accustomed to including technology in their curricula when Covid-19 forced a critical re-evaluation of the current practice. In a mere matter of days, the use of technology was not only a point for discussion anymore; it was lived. The ability of teacher educators to teach with technology had a direct impact on student success. Connectivity, access to suitable devices and sustainable training and support were now important considerations for teacher educators. The harsh reality soon became clear: Although some tertiary institutions could support pre-service teachers regarding access, connectivity and suitable devices, many students lacked the digital competencies to use the technology required for academic progress and success. It is evident that, in post-Covid-19 academia, the enhancement of digital competencies will remain a priority for teacher training programmes. The integration of digital competencies with content and pedagogical knowledge is essential for the successful training of future teachers. This article thus reflects on the efforts of a tertiary institution in South Africa to address the inclusion of technology in its curriculum through newly developed content that focuses on the enhancement of digital competency. Recommendations indicate that the effective inclusion of technology and digital competencies does not have to include major curricular changes but should rather become embedded within modules such as teaching practice.